A comparative study of stylistic kriging and Co - kriging Multivariate on the barley crop in Iraq - محمد جعفر موسى (Journal of Economics and Administrative Sciences, 2014)
This paper deals the prediction of the process of random spatial data of two properties, the first is called Primary variables and the second is called secondary variables , the method that were used in the prediction process for this type of data is technique Co-kriging , the method is usually used when the number of primary variables meant to predict for one of its elements is measured in a particular location a few (because of the cost or difficulty of obtaining them) compare with secondary variable which is the number of elements are available and highly correlated with primary variables, as was the application of the prediction process in a manner kriging only primary variables and we compared prediction result between C0-kriging and kriging technique to knowledge the best method for these cases.